NUMERICAL SIMULATION OF BIRDSTRIKE ON 19 PASSENGERS REGIONAL AIRCRAFT WINDSHIELD - Miftahul Firdaus - Nim: 13614032 , M
Bird strike or bird impact is a phenomenon of bird collision with aircraft components during operation, especially at take off and landing phase. Collision between birds and planes can cause serious damage to the structure of the aircraft. One of the components that experienced the most bird strike cases resulting in catastrophic is windshield. In this Final Project report, the author discusses numerical simulations of bird strike on N219 commuter windshields. The analysis was carried out by referring to the Federal Aviation Regulation (FAR 23). Bird mass and collision speed have been determined for the type of aircraft analyzed. The bird model used is an unimaterial hemispheric cylinder-shaped model with a mass of 0.91 kg (2 lbs), 180 mm long, and 90 mm in diameter. Bird density is set to 950 kg / m3. The approach used in the modeling is Smooth Particle Hydrodynamic method. In this method, the bird continuum is modeled as fluid particles that have certain mechanical characteristics. Birds move at a speed of 62 m/s relative to the plane and the angle of incidence is parallel to the plane's symmetry axis. In conducting numerical modeling, simulation, and analysis of this case, the author uses the Spaceclaim Direct Modeler, Hypermesh, and LS-Dyna software.